Risco na variação de preços agropecuários: um estudo para os mercados de soja, milho e boi gordo no município de Rio Verde-GO, 2004 a 2014 - Castro, Millades de Carvalho (2016)
Volatility in the prices of commodities and the financial return of agricultural activities affect the choice of what to produce. The present work investigates volatilities in prices of cattle, soybeans, and corn in Rio Verde (GO, Brazil), the choice of this region should be the importance of the city in the state and national agricultural production. For this study, we analyze weekly prices of corn, soybeans and cattle in Rio Verde spot market from 2004 to 2014, using Time Series Analysis and Value at Risk. The examination of the series pointed to the presence of a conditional variance. Therefore the ARCH / GARCH models were applied. The model selected to soybean was the IGARCH (2.1) and to corn and cattle the EGARCH (1.1). Due to disproportion between the traded prices and volumes it was not possible to perform the VAR series comparison. Therefore we used the ratio between the VAR and revenue of each product to compare between markets. Results showed a higher ratio for the cattle series indicating that volatility affects cattle producers’ income more than that of soybean or corn producers in Rio Verde (GO), which resulted in the reduction of this activity in the region.